Application of Geographical Information Systems in Sustainability in the Malaysian Context: A Review (Journal of Asian Geography, 2024)
The depletion of natural resources to meet growing demands for food, fuel, and fibre due to population growth and urbanisation has led to significant environmental damage in Malaysia. Hence, greenhouse gases have increased atmospheric greenhouse gas (GHG) levels, contributing to global warming and climate change. From developing software to analysing data, GIS is influenced by political, economic, and social factors throughout its production process. This paper introduces a structured framework aimed at conducting an extensive literature review study on the application of the Geographic Information System (GIS) to sustainability in Malaysia. The framework delineates essential steps and factors for identifying pertinent literature, assessing prior research, amalgamating outcomes, and pinpointing research voids. Adhering to this framework enables researchers to methodically scrutinise and appraise existing literature, furnishing a thorough depiction of the present state of knowledge within the application of GIS to sustainability in Malaysia. This literature review highlights GIS as a critical tool for promoting sustainable management across various domains, including flood hazard management, urban planning, agriculture, forest monitoring, transportation, air quality management, and water resource management, by providing access to data, models, and mapping.